ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS X SMA PADA SOAL BERBASIS ETNOMATEMATIKA - Erlanda Samuel Purba; Nurul Azmira Pane; Venesya Pitta Rezeki Siburian; Marcelly Claudia Sagala; KMA Fauzi (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
Low mathematical problem-solving ability among students on contextual questions serves as the primary background of this study. Ethnomathematics is regarded as an approach with the potential to create more meaningful learning experiences. This study aims to analyze the mathematical problem-solving ability of grade X high school students on ethnomathematics-based problems using a descriptive quantitative design. A total of 31 students were involved as subjects, each completing 5 essay questions embedded with local cultural contexts, analyzed based on Polya's problem-solving indicators. The findings indicate that students' abilities generally fall within the moderate category, with the largest proportion reaching 38.71%. The problem comprehension stage was relatively well-mastered; however, significant difficulties emerged in mathematical modeling, strategy formulation, procedural execution, and particularly in interpreting the final results. High-complexity problems proved more challenging to solve as they required the simultaneous integration of multiple concepts. The ethnomathematics approach helped students understand the problem context due to its relevance to daily life, yet it has not optimally fostered higher-order thinking skills. A more structured learning design is therefore needed to train mathematical modeling and reflective thinking in problem-solving. ABSTRAK Rendahnya kemampuan pemecahan masalah matematis siswa pada soal kontekstual menjadi latar belakang utama penelitian ini. Etnomatematika dipandang sebagai pendekatan yang berpotensi menciptakan pembelajaran lebih bermakna. Penelitian ini bertujuan menganalisis kemampuan pemecahan masalah matematis siswa kelas X SMA pada soal berbasis etnomatematika menggunakan desain deskriptif kuantitatif. Sebanyak 31 siswa dilibatkan sebagai subjek, masing-masing mengerjakan 5 butir soal uraian bermuatan konteks budaya lokal yang dianalisis berdasarkan indikator pemecahan masalah Polya. Hasil penelitian menunjukkan kemampuan siswa secara umum berada pada kategori sedang dengan proporsi terbesar 38,71%. Tahap pemahaman masalah relatif dikuasai dengan baik, namun hambatan signifikan muncul pada pemodelan matematis, penyusunan strategi, pelaksanaan prosedur, dan terutama penafsiran hasil akhir. Soal berkompleksitas tinggi terbukti lebih sulit diselesaikan karena menuntut integrasi beberapa konsep sekaligus. Pendekatan etnomatematika membantu siswa memahami konteks permasalahan karena dekat dengan kehidupan sehari-hari, namun belum secara optimal mendorong kemampuan berpikir tingkat tinggi. Diperlukan rancangan pembelajaran yang lebih terstruktur untuk melatih pemodelan matematis dan refleksi dalam penyelesaian masalah.